Long run cointegration between sector-specific indices and macroeconomic fundamentals / Jaafar Pyeman and Ismail Ahmad - Pyeman, Jaafar; Ahmad, Ismail (Faculty of Business and Management ; UiTM Press, 2007)
This paper has analysed the dynamic reactions between sector-specific indices of Bursa Malaysia and macroeconomic variables. This study shows that stock prices and macroeconomic variables tend to evolve as well as elaborate together in the long run. This study has identified various trends of responses among the sector-specific indices towards the innovation in macroeconomic variables. The share prices respond intensively to a shock in GDP in the long run particularly KLSECON, KLSEIND and KLSEFIN. The variances of share prices explained by innovation in GDP remain substantial for more than 20% in the long run for KLSECON and KLSEPROP. INFL has been identified to contribute great shock in KLSEFIN during short run and the share prices shocks for KLSEPROP towards innovation in INFL decrease in the long run. Furthermore, KLSEIND responds intensively to a shock in INFL and the effect has remained substantial in the long run. The innovation in INT has also contributed to great impact on the share prices especially KLSEFIN and KLSEIND during short run, KLSEIND has shown consistent responses to one standard deviation shock in INT for most of the quarters in this study. The results suggest that unanticipated changes in macroeconomic variables lead to similar patterns in some of the sector-specific indices with the effects differing mainly in term of the magnitude as well as the persistent of the responses that occur following the shocks.